Pengaruh Karakteristik Toko terhadap Pengalaman Konsumen Gerai Kopi - Sri Nathasya Br Sitepu; Angelica Irene Christina (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2020)
This research attempts to examine the impact of the coffee shop characteristics towards the consumers experience when they visit the coffee shop. The coffee shop characteristics including functional, atmosphere, design, and social characteristics. The population of this study are all Surabaya productive age residents, and the sample of this study was determined using Quota Sampling and the Isaac and Michael formula with the respondents requirements are those who had been visiting and/or consuming products directly at Starbucks Surabaya on maximum of 2 -3 months before filling out the questionnaire, with total of 384 respondents needed to be obtained. The questionnaire was distributed online and offline, with total 369 questionnaires are used in this study. This research uses SEM analysis. This research found that only the functional and social characteristics of the coffee shop have significant effect on the experience gained by its consumers; while the atmosphere and design characteristics have no significant effect, as the design characteristics have negative effect on the consumers experience. The practical contribution of research for the coffee shop owner are to maintains functional and social aspects as well as, improving aspects of design characteristics and atmosphere so that consumers gain experience when visiting.